Protective effect and economic impact of insecticide application methods on barley - Stoetzer, Alfred; Kawakami, Jackson; Marsaro Júnior, Alberto Luiz; Lau, Douglas; Pereira, Paulo Roberto Valle da Silva; Antoniazzi, Noemir (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the protective effect of different forms of insecticide application on the transmission of yellow dwarf disease in barley cultivars, as well as to determine the production costs and the net profit of these managements. The experiments were carried out during 2011 and 2012 growing seasons, using the following managements at main plots: T1, seed treatment with insecticide (ST) + insecticide on shoots at 15‑day interval; T2, just ST; T3, insecticide applied on shoots, when aphid control level (CL) was reached; T4, without insecticide; and T5, ST + insecticide on shoots when CL was reached. Different barley cultivars – BRS Cauê, BRS Brau and MN 6021 – were arranged in the subplots. Insecticides lambda cyhalothrin (pyrethroid) and thiamethoxam (neonicotinoid) were used. There were differences on yellow dwarf disease index in both seasons for the different treatments, while damage to grain yield was influenced by year and aphid population. Production costs and net profit were different among treatments. Seed treatment with insecticide is sufficient to reduce the transmission of yellow dwarf disease in years with low aphid population pressure, while in years with larger populations, the application of insecticide on shoots is also required.